First Order Space Time Autoregressive Stationary Model on Petroleum Data - Khafsah Joebaedi; K Parmikanti; Badrulfalah Badrulfalah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
First order Space-Time Autoregressive model is one of the models which involves location and time. STAR(1;1) model stationary can be used to forecast future observation at a location based on one previous time of its own location and the spatial neighborhood. STAR(1;1) model on petroleum productivity data in Balongan, Indramayu, West Java with eigenvalue less than 1. It indicates that STAR (1;1) model on petroleum productivity data in Balongan, Indramayu, West Java meets the stationary requirement